Treatment of Recurrent Wide Neck Bifurcation Aneurysm With the Barrel Vascular Reconstruction Device - Sirakov, Stanimir; Panayotova, Adriana; Sirakov, Alexander; Minkin, Karsimir; Ninov, Kirstian; Raychev, Radoslav (Frontiers in Neurology, 2019)
We present a case of successful embolization of a recurrent wide neck bifurcation aneurysm with a Barrel vascular reconstruction device (VRD). The unique properties of this novel device allowed optimal aneurysm neck coverage during third consecutive re-treatment, ultimately resulting in complete aneurysm obliteration. The parent vessel anatomy and the neck morphology of the aneurysm, in combination with a presence of a large pre-existing coil mass, were ideal for Barrel stent placement. The expanded portion of the device conformed perfectly to the recanalized aneurysm neck, providing optimal support for additional coil embolization. This case illustrates the advantages of Barrel VRD for definitive embolization of large, recurrent, and previously coiled wide-neck bifurcation aneurysm as a reasonable alternative to other traditional treatment modalities, such as flow diversion or Y and X stenting.